INNOVATIVE METHODS FOR ENHANCING CREATIVE THINKING IN FINE ARTS EDUCATION - Ismoilov Otabek Shavkat o‘g‘li (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines innovative methods for developing students’ creative thinking in fine arts education. It highlights the use of interactive lessons, project-based activities, digital tools, and student-centered approaches to enhance artistic perception, problem-solving skills, and aesthetic judgment. The study emphasizes fostering a learning environment that encourages originality, experimentation, and collaboration, thereby supporting holistic artistic development.